Bimetallic Oxide Hollow Structures Induced by Surface Coordination of ZIF‐67. Issue 46 (3rd December 2019) - Zhao, Kaixuan; Guo, Jinxin; Wei, Huiying; Yang, Yanzhao
Abstract : Bimetallic hollow nanomaterials which are composed of two different metal/metal oxide materials show great potentials owing to their unique structural features. Here, the second metal ions were introduced into the surface of ZIF‐67 by ultrasonication to form bimetallic hollow complexes, and the coordination between the second metal ions and ZIF‐67 colloidal crystals are further investigated. A series of bimetallic complexes has been synthesized by incorporating Fe III, Cu II and Ni II into the coordinating block of ZIF‐67. After calcination in oxygen, these as‐prepared transformed to Fe/Cu/Ni doped Co3 O4 hollow nanoboxes. We found a facile and general method to form bimetallic complexes by complexing the second metal ions with ZIF‐67 surface ligands and calcining to form bimetallic hollow nanoboxes. Abstract : A new coordination method for the preparation of hollow bimetallic oxides is proposed. The unsaturated ligands of ZIF‐67 were combined with the second metal ions by ultrasound, and then calcined to form a hollow bimetallic hollow nanoboxes. This method can be applied to Cu II, Fe III, Ni II and other metal ions.